Pharmacological vector of Rudolf Buchheim - Konstantin M. Reznikov (Belgorod National Research University, 2019)
The paper presents materials about the role of Professor Rudolf Buchheim in the origin and development of experimental pharmacology in our country. He was the first in the world who established Institute of experimental pharmacology at University of Dorpat in 1849 which for many years was the only one in the world and which became the basis for the creation of departments of pharmacology. As the main principles of scientific pharmacology he considered the use of objective classification of drugs, which he developed and which is still the basis for modern classifications, and as the second principle he proclaimed a detailed establishment of changes in the living organism, arising after the administration of drugs. As a man of talent and a great organizer, he made a significant contribution to the development of pharmacological science. Such receivers as Schmiedeberg, Boehm, Hans Horst Meyer, Kobert, as well as all scientists whose activities are associated with his name based on the scientific pedigree were guided by his scientific ideas. In 1918 University of Dorpat was moved to Voronezh, where Department of pharmacology was first headed by prof. D.M. Lavrov, and then later prof. Vorontsov, who are the bearers of the traditions of University of Dorpat, also arrived from Dorpat. Despite the economic hardships they, as well as apprentices prof. V.N. Vorontsov, V.I. Zavrazhnov, and later his student prof. Reznikov carefully preserved and multiplied the achievements of experimental pharmacology, successfully implementing the most important principles of this section of medicine, formulated by prof. Buchheim more than 100 years ago.